Turismo social y turismo receptivo. Dinámicas competitivas y cooperativas a partir de la Nueva Ley de Turismo en Argentina1 (2018)
The research analyzes the competitive and cooperative dynamics promoted by the New Tourism Law (25.997 / 05) related to the promotion of social tourism and the strengthening of receptive tourism. Within the new law, tourism is recognized as a right of the people and according to this framework, the foundations are laid for the promotion of social tourism policies. At the same time, receptive tourism is highlighted as a non-traditional export activity, promoting different tools for its endorsement. Although this institutionalized complementarity, research shows that the importance acquired by receptive tourism (in the execution of resources, the creation of specific organizations and the appointment of personal) goes against the social tourism policy, which ends up occupying a marginal place in the tourist agenda.